Feasibility of high-frequency alternating current power for motor auxiliary loads in vehicles - Antaloae, Ciprian C.; Marco, James; Vaughan, Nicholas D. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a feasibility study into the application of a 100-V, 50-kHz high-frequency ac (HFAC) network for powering automotive electrical auxiliaries. The study is focused on motor-actuated loads and is divided into two sections. First, the investigation indicates the benefits of replacing low-torque dc motors with lighter and more efficient 400-Hz ac machines for applications such as electric fans, fuel pumps, or blower motors. A comparative examination of commercially available machines indicates space and weight reduction of more than 60%, and efficiency savings between 25% and 100% are possible. Second, the inquiry evaluates the viability of replacing existing dc/ac inverters with HFAC/ ac converters for high-torque ac machines as employed, for example, in electric- power-assisted steering (EPAS) or heating, ventilation, and air conditioning systems. Based on experimental and simulation results for a column-assist EPAS application employing a three-phase permanent-magnet synchronous motor, this paper shows that an HFAC drive is expected to reduce the voltage harmonic content below 50 kHz by at least 10% compared with the dc/ac inverter. However, the disadvantages of the former drive make it less attractive than the existing dc/ac circuit. Specifically, the EPAS motor torque ripple is expected to be approximately 2% higher compared with the dc counterpart drive. Further drawbacks of the HFAC/ac drive include high metal-oxide-semiconductor field-effect transistor (MOSFET) conduction losses, higher voltage harmonics above 50 kHz, and complex control requirements of the inverter. Conclusively, significant HFAC advantages for motor loads can only be attributed to machines with a nominal torque capability that is limited to 2 N ·m. However, given the number of such devices within a typical vehicle, this translates into a possible vehicle mass saving of 30 kg and a potential reduction in fuel consumption by 0.8 L/100 km